Integration of MTC and satellites for IoT toward 6G era - Alves, Hirley; Hoyhtya, Marko; Mikhaylov, Konstantin; Ohio Library and Information Network (Hoboken, New Jersey : Wiley, 2024)
"This book is the first one focusing on the integration of machine-type communications (MTC) and satellite connectivity toward the 6th generation of mobile systems (i.e., the "6G"). Integrating these two technologies, especially within the emerging direct-to-satellite (DtS) concept employing direct connectivity between an MTC terminal and a satellite-based gateway, will be critical in enabling the future Internet of Things (IoT) applications in remote areas with limited connectivity infrastructure available. To this end, the book delivers an in-depth analysis of the drivers, use cases, scenarios, technical aspects, cybersecurity, and mechanisms spanning from the physical layer (PHY) to the application layer, regulation, standardization, and potential business models. In addition, many examples, illustrative figures, and tables support the text"--
Machine-type communications, the internet of things, and satellite networks : drivers, use-cases, and requirements
Includes bibliographical references and index
Keywords: 6G mobile communication systems; Artificial satellites in telecommunication; Internet of things